Faktor –Faktor Yang Mempengaruhi Cakupan Penggunaan Informasi Akuntansi Pada Koperasi Di Provinsi Daerah Istimewa Yogyakarta - Sungkono Sungkono (EBBANK, 2010)
Accounting information should be used by interested constituents  (stakeholders) as one of the basic for business decision making. In fact, accounting information has not been used optimally, especially by the principals of SMEs, including cooperatives. Many factors influence the extent of usage of accounting information, namely the scale of business, the age of  business ,the  type of business, manager education and training of accounting. This article presents the results of research on the factors that influence the extent of the usage of accounting information by the cooperative, which examines how the influence of scale, age, business and accounting training influence the extent of the usage of accounting information by the cooperativse. This research take  sample  of 30 cooperatives in the district of Bantul by purposive random sampling. The hypothesis was tested with multiple regression test showed that the three factors, namely the scale of business, age of business and accounting training both totally and partially influence the extent of the usage of accounting information by the cooperatives.